Spectroscopic Analysis of Sparfloxacin Release Pattern from the Cellulose Derivative Bases - Parthasarathy, V.; Manavalan, R. (Asian Journal of Chemistry, 2012)
Ultraviolet/visible and infrared studies were carried out with the mixture of sparfloxacin and various polymer bases namely, ethyl cellulose: polyethylene glycol (EC:PEG), ethyl cellulose:hydroxy propylmethyl cellulose (EC:HPMC) and ethyl cellulose:eudrajit (EC:EUD). The amount of drug release for every 24 h was estimated through UV/visible spectroscopy. The study showed that the drug release rate is related to the binding of the drug to the base. The IR spectrum of the samples provides the information about the strength of bonding between the drug and bases.